8 Environment enrichment reduces aggression and stereotypic behaviors in feedlot steers. (29th July 2019) - Park, Rachel M; Bova, Rachel; Jennings, Jenny S; Daigle, Courtney L
Abstract: Feedlots provide limited environmental complexity to cattle – a highly curious and social species. In the absence of adequate stimulation, cattle may engage in aggressive or abnormal behaviors. Implementation of biologically appropriate and species specific environmental enrichment (EE) has the potential to enhance welfare of feedlot steers. The objective of this study was to identify behavioral differences between cattle exposed to EE compared to those without. Composite steers (n = 54) were assigned to one of two treatments: 1) No enrichment (CON; n = 3 at 9 head/pen) and 2) BRUSH (cattle brush; n = 3 at 9 head/pen). Video recordings were decoded utilizing continuous observation for the frequency and duration of headbutting, mounting, kicking, bar licking, tongue rolling, allogrooming, and brush usage from 0800 to 1730 on d -2, -1, 0, 1, 2, 4, 8, 16, 32, and 64 relative to brush implementation. Impact of day, treatment and their interaction on cattle behavior was evaluated using a Generalized Linear Mixed Model (PROC MIXED) in SAS. (BRUSH) steers spent less time bar licking (P = 0.023) and engaged in bar licking less frequency (P = 0.005) than CON throughout the duration of the study. Compared to CON, BRUSH steers performed fewer headbutts across the duration of the study (P = 0.004). Brush usage frequency (P = 0.0002) and duration (P = 0.008) were greatest on d 0 compared to all other research days. The frequency (P = 0.0006) and duration (P = 0.0002) of tongue rolling increased with research day. Similarly, the frequency (P = 0.0001) and duration (P = 0.002) of allogrooming increased over time; however, there was a decrease in allogrooming on d 64. Mounting frequency was impacted by research day and peaked at d 8 (P = 0.002). BRUSH cattle performed less stereotypic and aggressive behaviors suggesting that EE is beneficial for feedlot cattle welfare